Accounting Interpretation of Current Biological Assets - Rupska, Teodora (Research Papers, 2009)
It is investigated theoretical and methodological problems in accounting interpretation of current biological assets. They are specific object of management, because they have biological nature. The biological transformation is typical for them, but it is specific in comparison with the other biological assets.The plants are not including in current biological assets for a long time in Bulgaria. It is offered plants to be added to them, because they correspond to the definition of biological asset. The risk is typical for current biological assets more than the other biological assets. It is investigated specific risk and it is present strategies of them management.There are problems of accounting interpretation of current biological assets. Some of them are result of evaluating in fair value and the appearing of differences. There are different models of accounting reflect of the differences in the dissertation. It is done models of declare of strategies of risk management for current biological assets in financial reports.The other problem is that the part of accounts used for recording of current biological assets in practice used for recording of fixed biological assets. It is offered to change the names of some.